Gender differences in the association between smoking and the risk of suicide in depressed patients: a longitudinal national cohort study - Jang, Yoo Jin; Kim, Hyewon; Jung, Jin-Hyung; Han, Kyungdo; Jeon, Hong Jin (Frontiers in Psychiatry, 2025)
IntroductionAlthough the gender differences in suicide and smoking are well-known, studies exploring the impact of gender on the relationship between smoking and suicide are limited. This population-based nationwide cohort study examines the association between smoking and suicide risk among1.8 million depressed patients, analyzed separately by gender.MethodsThis longitudinal cohort study included 1,827,249 adults diagnosed with depression between 2010 and 2015 from the Korean National Health Insurance Service database. Smoking status (never, former, current) was self-reported during health screenings, and suicides were identified via national mortality records. Cox proportional hazards models adjusted for demographic, clinical, and psychiatric covariates assessed hazard ratios (HRs) for suicide risk. Subgroup analyses explored effect modifications by covariates, including age, income, and alcohol use.ResultsOver a median follow-up of 6.8 years, 6,318 individuals (0.35%) died by suicide. Smoking was associated with increased suicide risk in both men and women, with a stronger association in women. Current smoking showed a higher risk in women (HR = 2.646, 95% CI: 2.287-3.062) compared to men (HR = 1.376, 95% CI: 1.277-1.483). In men, factors such as younger age and alcohol consumption intensified this association, whereas in women, low income was a significant modifier; the highest suicide risk was observed in low-income former smokers.ConclusionSmoking is associated with increased suicide risk among individuals with depression, with notable gender differences in risk magnitude and modifying factors. These findings highlight the need for gender-specific suicide prevention strategies. Limitations include reliance on self-reported smoking data and lack of time-varying measures of exposure.